Imaging of Radiation Accidents and Radioactive Contamination Using Scintillators - Ogawa, Tomoya; Sarukura, Nobuhiko; Watanabe, Masahito; Fukuda, Tsuguo; Nango, Nobuhito; Arikawa, Yasunobu; Yamanoi, Kohei; Nakazato, Tomoharu; Cadatal-Raduban, Marilou; Shimizu, Toshihiko; Nakai, Mitsuo; Norimatsu, Takayoshi; et al. (IntechOpen, 2011)
None